Criminal liability for obstructing the legal activity of a defense counsel in court proceedings - Ostafiichuk, Liudmyla; Akimov, Mykhailo O; Goncharuk, Olga V.; Shulh, Andriy O.; Tretiakov, Dmytro A. (My University, 2022)
A fair trial is guaranteed by the efficient work of a lawyer aimed at protecting the client accused of committing an offense and the state protection of advocacy. The purpose of the study was to determine the criminal law protection aimed at ensuring the safeguarding the defense counsel’s activity in court proceedings considered in the context of international standards. Empirical and theoretical methods of research, as well as the method of comparative analysis were used for a comprehensive consideration of the subject. The grounds for criminal liability for obstructing the legal activity of the defense counsel in court proceedings are elaborated. Criminal liability for a crime against justice may take the form of a fine, corrective labor, imprisonment or suspension from office. The protection of the lawyers’ rights and international guarantees of safe advocacy involves the adoption of measures at the state level that will enable lawyers to perform their professional duties without intimidation, pressure, obstruction and interference, as well as measures to eliminate the administrative, economic or other sanctions. Further research will address the advocacy security to determine and substantiate the effective means of its criminal protection.
Кримінальна відповідальність за перешкоджання юридичній діяльності захисника у судовому розгляді
Keywords: defense counsel; obstruction; advocacy; legal aid; intervention; liability